2012
DOI: 10.3354/cr01083
|View full text |Cite
|
Sign up to set email alerts
|

Legacies of pre-industrial land use can bias modern tree-ring climate calibrations

Abstract: In Scandinavia, dendrochronological reconstructions of past climate have mostly been based on tree-ring data from forests in which there has been, supposedly, very little or no human impact. However, human land use in sub-alpine forests has a substantially longer history and more profound effects on the forest ecosystems than previously acknowledged. Therefore, to assess human influence on tree-ring patterns over the last 500 yr, we have analyzed tree-ring patterns using trees from 2 abandoned Sami settlements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…While previous research has indicated potential challenges in smaller comparisons (Clauson & Wilson, ; De Ridder et al, ; Gunnarson et al, ; Helama et al, ; Ivkovich & Koshy, ; Mannes et al, ; Melvin et al, ; Park & Telewski, ), our results firmly consolidate that the mxd measurement in practice continues to be inherently dependent on measurement idiosyncrasies despite the fact that the anatomical principle of mxd having been defined (Vaganov et al, ). This awareness requires that when building mxd chronologies for climate reconstructions aiming to preserve multi‐centennial variability (e.g., Cook et al, ), data combined from different laboratories or techniques must at a minimum be scaled to a common mean and standard deviation prior to amalgamation (Esper et al, ; McCarroll et al, ; Melvin et al, ; Zhang et al, ).…”
Section: Synthesis Of Empirical Findings and Existing Knowledgesupporting
confidence: 79%
See 1 more Smart Citation
“…While previous research has indicated potential challenges in smaller comparisons (Clauson & Wilson, ; De Ridder et al, ; Gunnarson et al, ; Helama et al, ; Ivkovich & Koshy, ; Mannes et al, ; Melvin et al, ; Park & Telewski, ), our results firmly consolidate that the mxd measurement in practice continues to be inherently dependent on measurement idiosyncrasies despite the fact that the anatomical principle of mxd having been defined (Vaganov et al, ). This awareness requires that when building mxd chronologies for climate reconstructions aiming to preserve multi‐centennial variability (e.g., Cook et al, ), data combined from different laboratories or techniques must at a minimum be scaled to a common mean and standard deviation prior to amalgamation (Esper et al, ; McCarroll et al, ; Melvin et al, ; Zhang et al, ).…”
Section: Synthesis Of Empirical Findings and Existing Knowledgesupporting
confidence: 79%
“…The Itrax multiscanner by Cox Analytical Systems (Sweden) was mainly, but not exclusively, developed for wood samples-the functionality permits the analysis of speleothems and other small flat samples and additionally offers information about chemical composition of the samples when equipped with an X-ray fluorescence detector (Hevia et al, 2018;Scharnweber et al, 2016). Available since 2004, an increasing number of laboratories (at present 15) have used the Itrax multiscanner to produce density data for a number of dendroecological and/or dendroclimatological studies (e.g., Björklund et al, 2015;Björklund et al, 2013;Cameron et al, 2015;Duan & Zhang, 2014;Gunnarson et al, 2011;Gunnarson et al, 2012;Helama et al, 2014;Liang et al, 2016;Linderholm et al, 2015;Melvin et al, 2013;McCarroll et al, 2013;Xing et al, 2014;Zhang et al, 2015Zhang et al, , 2016. Many of these studies combine new or updated measurements with previously published MXD data acquired by other analytical techniques such as the Walesch technique.…”
Section: The Itrax Multiscannermentioning
confidence: 99%
“…Disturbance frequency in nonclassical forests, however, could be a less surmountable limitation. Land-use legacies could degrade the climatic signal in surviving trees (Gunnarson et al 2012). We see some indication of this here.…”
Section: Limitations: Longevity Disturbance and Low-frequency Informentioning
confidence: 75%
“…The impact of disturbance related to human activity on forest ecosystems is not uncommon and has been reported for example in Scandinavia even in areas considered undisturbed (Josefsson et al , ) and has been shown to affect the climate signal in RW chronologies from such locations (Gunnarson et al , ). Rydval et al () identified the presence (and succeeded in reducing the influence) of disturbance‐related growth release trends in several Scots pine RW chronologies which were attributed to a history of extensive woodland timber extraction over several centuries in Scotland.…”
Section: Methodsmentioning
confidence: 99%